Extending Microsoft Dynamics NAV 2016 cookbook : make the most of your NAV deployment by extending and customizing it with a variety of expert tools /: make the most of your NAV deployment by extending and customizing it with a variety of expert tools. (2017) - Drogin, Alexander
No abstract available